Religion, State, and Society: Jefferson's Wall of Separation in Comparative Perspective - Jelen, Ted G. (A journal of church and state, 2010)
The eleven essays which comprise this volume originated at a conference held in March 2007 at Prague. The conference was sponsored by the Robert H. Smith International Center for Jefferson Studies. The purpose of the conference, and the resulting edited collection, was to analyze the separation of church and state in the United States and in other settings, using Thomas Jefferson's metaphor of a “wall of separation” as an intellectual springboard., The volume is divided into three parts. The first, which contains essays by Peter Onuf, Jack R. Rakov, Robert M. O'Neil, and A. E. Dick Howard, ostensibly analyzes issues associated with church-state separation in the United States, although Howard's essay applies the “wall” metaphor to other settings, such as Australia and Canada.